Maternal preconception lipid profile and gestational lipid changes in relation to birthweight outcomes - Bever, Alaina M. (Sci Rep, 2020)
In 575 women with 1–2 prior pregnancy losses; total cholesterol, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) were evaluated preconception and throughout pregnancy to evaluate whether previously observed associations between third trimester maternal lipid profile and birthweight outcomes are driven by preconception lipids or lipid changes during pregnancy. Lipid trajectories were compared by pre-pregnancy body mass index (BMI) <25 or ≥25 kg/m(2); logistic regression models evaluated preconception lipid concentration and change from preconception to 28 weeks with adjusted odds of large- or small-for-gestational age (LGA or SGA) neonate by BMI group. Preconception lipid concentrations and gestational lipid trajectories varied by BMI group (P < 0.001). Preconception lipids were not associated with LGA or SGA in either group. A 10 mg/dL increase in HDL-C change from preconception to 28 weeks was associated with decreased odds of LGA (odds ratio (OR) = 0.63, 95% confidence interval (CI): 0.46, 0.86) and 10 mg/dL increase in TG change associated with increased odds of LGA (OR = 1.05, 95% CI: 1.01, 1.1) overall. For ≥25 BMI only, 10 mg/dL increase in HDL-C change was associated with decreased SGA odds (OR = 0.35, 95% CI: 0.19, 0.64). Gestational lipid trajectories differed by BMI group and were differentially associated with birthweight outcomes, with HDL-C more strongly associated with healthy birthweight in women with BMI ≥25.